2020
DOI: 10.1088/1748-0221/15/07/c07036
|View full text |Cite
|
Sign up to set email alerts
|

CYGNO: a gaseous TPC with optical readout for dark matter directional search

Abstract: The CYGNO project has the goal to use a gaseous TPC with optical readout to detect dark matter and solar neutrinos with low energy threshold and directionality. The CYGNO demonstrator will consist of 1 m3 volume filled with He:CF4 gas mixture at atmospheric pressure. Optical readout with high granularity CMOS sensors, combined with fast light detectors, will provide a detailed reconstruction of the event topology. This will allow to discriminate the nuclear recoil signal from the background, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…TPCs have been in use since the late 1970s, typically with the direct readout of the drifted charge. CCD optical readout of time projection chambers was first demonstrated in ∼1990 by [7][8][9], and it has more recently been developed by the DMTPC project for direction-sensitive dark matter searches [10], by the CYGNO collaboration [11], by an optical TPC for precision nuclear physics cross section measurements [12], for Xray imaging [13], for proton imaging [14], and by the CERN gas detectors group for radiography using X-rays [15]. DMTPC demonstrated that a TPC with optical readout can realize a sub-mm 2 segmentation over a readout plane with an area larger than 1 m 2 [16].…”
Section: Optical Readoutmentioning
confidence: 99%
“…TPCs have been in use since the late 1970s, typically with the direct readout of the drifted charge. CCD optical readout of time projection chambers was first demonstrated in ∼1990 by [7][8][9], and it has more recently been developed by the DMTPC project for direction-sensitive dark matter searches [10], by the CYGNO collaboration [11], by an optical TPC for precision nuclear physics cross section measurements [12], for Xray imaging [13], for proton imaging [14], and by the CERN gas detectors group for radiography using X-rays [15]. DMTPC demonstrated that a TPC with optical readout can realize a sub-mm 2 segmentation over a readout plane with an area larger than 1 m 2 [16].…”
Section: Optical Readoutmentioning
confidence: 99%
“…Preliminary evaluation of the expected CYGNO PHASE-1 backgrounds has been performed with a Geant-4 [36] based Monte Carlo simulation. An external passive shielding of 2-m Water + 5 cm copper has been identified as the optimal configuration to reduce the number of expected ERs from LNGS environmental gamma and neutron fluxes below 10 3 cpy (with O(1) cpy nuclear recoils) in the range 0-20 keV [37]. The GEMs foil, the gas vessel PMMA, and the camera body and lens, expected to introduce the largest radioactivity contamination from internal components, have been measured with HPGe gamma spectroscopy detectors.…”
Section: The Cygno Phase-1 Detectormentioning
confidence: 99%
“…The effectiveness of THGEMs has resulted in their widespread use within the contemporary TPC field, and much development has been made including the production of liquid hole multipliers and FAT GEMs [4]. TPCs are now integral within the neutrino and dark matter sectors, with the proposed kiloton scale DUNE modules [5][6][7][8][9][10][11], CYGNO [12], DarkSide-20k [13], ArDM [14] and LZ [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the abrasive machining process is no longer subject to drill bit wear, potentially improving hole diameter consistency across the THGEM. The abrasive machining manufacturing process could have far reaching consequences within the neutrino and dark matter sectors [12][13][14][15]20], as well as in medical imaging [21].…”
Section: Introductionmentioning
confidence: 99%